النظام القانوني لاندماج الشركات وآثاره القانونية: دراسة مقارنة - أرباب، يوسف زكريا عيسى (جامعة النيلين - كلية الدراسات العليا, 2019)
The study cast light on the legal system for the corporate mergers , and its effect on the integrated companies, a comparative study, where the company emerging becomes more important for many reasons on the view of the controversy life, it is a position of legal, juristic, economic attention, the researcher studied analytically the definition of company emerging which is a contract between two or established companies, it is the merging project, the companies agreed according to that to emerge by consolidation, so the legal capacity of the integrated company will removed, or by mixing the two companies to produce a new company where the personality to the two companies was removed. The researcher obtains many results the important of which is: the result of company emerging termination of the integrated company and removal of its personality's, losing of its capacity in judiciary. The emerging also effects on the rights of the integrated company inclusion and shareholders, where it lead to hiding of these companies, and replacing it capacity by the new company, that will be through the integrated company competitors, in satisfying of their rights, the study recommends the Sudanese legislative to stipulate on the results effects of emerging clearly , regarding what related to the rights and obligations of the integrated company to the new one, because it is considered a legal substitution by attention. It also recommends the Sudanese legislative to amend the article No (130) from the Sudanese company law for the year 2015, by omitting the word( it is possible) that stipulated in the article and replaced by the word (it should) because the emerging will lead to removal of the legal personality of the company, subsequently, it cannot be judged or sentenced, therefor to transfer the rights and the company obligations to the new company or new body in case of the company emerging and confirmation of a new company.
تناولت هذه الدراسة النظام القانوني لاندماج الشركات وأثره على الشركات المندمجة، دراسة مقارنة، حيث أضحى الاندماج بين الشركات ظاهرة اقتصادية لها أسبابها في ظل الحياة المعاصرة، وهو محل الاهتمام الاقتصادي والفقهي والقانوني. درس الباحث بالتحليل تعريف اندماج الشركات، فاندماج الشركات هو عقد بين شركتين أو أكثر قائمتين من قبل، يسمى مشروع الاندماج، تتفقان بموجبه على الاتحاد بينهما عن طريق الضم فتزول بموجبه الشخصية القانونية للشركة المندمجة، أو عن طريق المزج بين الشركتين فتنشأ شركة جديدة مع زوال الشخصية القانونية للشركتين. وتناول الباحث صور الاندماج وتقسيماته حسب اختلاف وجهة نظر الفقه القانوني إليه، وبين الطبيعة القانونية للاندماج، كما تناول الباحث الآثار القانونية المترتبة على الاندماج، سواء من حيث أثره على الشركة المندمجة، أو بالنسبة للشركة الدامجة، أو الناتجة عن الاندماج، أو أثره على العقود المبرمة من قبل الشركة أو الشركات المندمجة. أتبع الباحث المنهج الاستقرائي التحليلي المقارن، توصل الباحث إلى جملة من النتائج والتوصيات أهمها: يترتب على الاندماج انقضاء الشركة المندمجة وزوال شخصيتها المعنوية، وفقدانها أهليتها في التقاضي. كما يؤثر الاندماج في حقوق دائني الشركات المندمجة وحملة سنداتها، حيث أنه يؤدي إلى اختفاء هذه الشركات، وحلول الشركة الدامجة أو الجديدة محلها في الوفاء بهذه الديون. كما يؤثر في حقوق دائني الشركة الدامجة وحملة سنداتها، وذلك من خلال مزاحمة دائني الشركات المندمجة وحملة سنداتها لهم في استيفاء حقوقهم من الشركة الدامجة. وأوصت للمشرع السوداني بالنص على الآثار المترتبة على الاندماج بكل وضوح فيما يتعلق بانتقال حقوق والتزامات الشركات المندمجة إلى الشركة الدامجة أو الناتجة عن الاندماج باعتبارها خلفا قانونيا بالاهتمام. كما أوصت للمشرع السوداني بتعديل نص المادة (130) من قانون الشركات السوداني لسنة 2015 م وذلك عن طريق حذف كلمة (يجوز) الواردة في هذه المادة والاستعاضة عنها بكلمة (يجب) وذلك لأن الاندماج يؤدي إلى زوال الشخصية القانونية للشركة أو الشركات المندمجة وبالتالي لا يمكن أن تقاضي أو تقاضى، كذلك لانتقال حقوق والتزامات الشركة أو الشركات المندمجة للشركة الدامجة أو للكيان الجديد في حالة اندماج شركات وتكوين شركة جديدة.
Keywords: الشركات -- اندماج الشركات -- الشركات المندمجة -- الشركات الدامجة -- القانون السوداني